DATE CORRECTION OF OMAR BIN KHATTAB’S DEATH IN AN ASTRONOMICAL PERSPECTIVE - Akhmad Nadirin; M. Ihtirozun Ni'am (Al-Hilal: Journal of Islamic Astronomy, 2019)
Omar bin Khattab was a companions of Prophet Muhammad SAW who had the title as Amīr al-Mu’minīn. He led Islam for about 10 years before being stabbed by Abu Lu'luah when he was in the morning prayer at the end of the 23rd H year until death.  There are many opinions in Islamic historical literature about the death of Omar bin Khattab.  Some experts say that 3, 4 or 7 days left in Dzulhijjah 23 H or the Sunday of Muharram 24 H. This study is intended for the first, knowing why there is a difference in the death data. Second, answering the problems of correction Omar bin Khattab’s death data in an astronomical perspective. These problems are discussed with a qualitative research in the form of library research.  The primary sources used in this study are Tārikh al-Thabari Tārikh al-Umam wa al-Mulūk, Ashāb al-Futuyā , al-Kāmil fī al-Tārikh, Siyar A’lam al-Nubulā, al-Bidāyah wa al-Nihāyah. Furthermore, the data obtained is converted into days and dates then it is cohered with the appropriate data. The result of this study shows that there is the difference of Omar bin Khattab’s death data. It is caused by the difference theories of the data. Thus, based on the astronomical calculation, the date of Omar bin Khatab’s death was on Wednesday, 26th Dzulhijjah 23 H / 3rd of November 644 M (3 days left in the month Dzulhijjah 23 H).